2017
DOI: 10.1038/s41598-017-00199-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Prevented High-Fat Diet-Induced Obesity and Improved Insulin Resistance in Mice

Abstract: Obesity and its associated chronic inflammation in adipose tissue initiate insulin resistance, which is related to several pathologies including hypertension and atherosclerosis. Previous reports demonstrated that circulating hepatocyte growth factor (HGF) level was associated with obesity and type 2 diabetes. However, its precise role in obesity and related-pathology is unclear. In this experiment, cardiac-specific over-expression of human HGF in mice (HGF-Tg mice) which showed 4–5 times higher serum HGF leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…inhibiting immune cell infiltration and inflammation in tissues [8,26]. We found that HGF-Tg mice presented less weight loss, less epithelial ulceration and less infiltration of Ly6G+ neutrophils as shown by histological and immunohistochemical observation on day 5.…”
Section: Recent Studies Have Described the Indispensable Contributionmentioning
confidence: 56%
See 1 more Smart Citation
“…inhibiting immune cell infiltration and inflammation in tissues [8,26]. We found that HGF-Tg mice presented less weight loss, less epithelial ulceration and less infiltration of Ly6G+ neutrophils as shown by histological and immunohistochemical observation on day 5.…”
Section: Recent Studies Have Described the Indispensable Contributionmentioning
confidence: 56%
“…Inflammation cytokines mediate complex functions in traumatic ulcers, depending on their proportional concentrations [15,30,31]. HGF maybe a new drug target to treat metabolic disease by inhibiting the inflammation cytokines in adipose tissue in HGF-Tg mice [26]. Anti-inflammatory roles of HGF have been described, including inhibiting pro-and inflammatory cytokines such as TNF-ɑ, IFNγ,TGF-βand iNOS.…”
Section: Recent Studies Have Described the Indispensable Contributionmentioning
confidence: 99%
“…In addition, cardiacspecific overexpression of HGF resulting in a fourfold increase in circulating HGF levels is sufficient to protect mice from highfat diet-induced body weight gain and insulin resistance. These mice also demonstrate reduced accumulation of macrophages and reduced levels of inflammatory factors in white adipose tissue compared to wild-type mice (Muratsu et al, 2017). Consistent with the improved glucose tolerance when overexpressed, a HGF-neutralizing antibody in wild-type mice exacerbated the symptoms of diet-induced obesity and impaired glucose clearance ability, but the tissues responsible for this phenotype were not identified (Muratsu et al, 2017).…”
Section: Hepatocyte Growth Factor (Hgf)mentioning
confidence: 87%
“…These mice also demonstrate reduced accumulation of macrophages and reduced levels of inflammatory factors in white adipose tissue compared to wild-type mice (Muratsu et al, 2017). Consistent with the improved glucose tolerance when overexpressed, a HGF-neutralizing antibody in wild-type mice exacerbated the symptoms of diet-induced obesity and impaired glucose clearance ability, but the tissues responsible for this phenotype were not identified (Muratsu et al, 2017). Mechanistically, activation of the HGF/MET pathway increases glucose uptake in peripheral metabolic organs and stimulates insulin secretion in pancreatic β-cells.…”
Section: Hepatocyte Growth Factor (Hgf)mentioning
confidence: 89%
See 1 more Smart Citation